2012
DOI: 10.18860/jt.v2i1.1832
|View full text |Cite
|
Sign up to set email alerts
|

Pembelajaran Geometri Sesuai Teori Van Hiele

Abstract: AbstrakGeometry has a special place in the math curricula at schools. This is because the contents of geometry considered usefel in the daily life. Based on the fact, many students faced difficulties to understand the geometry theory. For this purpose, this article offered van Hielle teory as one of alternative to solve the students' problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
20

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 2 publications
(2 reference statements)
1
15
0
20
Order By: Relevance
“…The purpose of learning geometry at school as reported by Thomas [3], such (a) to develop spatial awareness, intuition and the ability to visualize geometry; (b) To provide the breadth of experience both in the geometry of two-dimensional space and 3-dimensional; (c) To develop knowledge and understanding and the ability to use the properties and geometry theorem; (d) to encourage the development and use of conjecture, deductive reasoning and evidence; (e) To develop the application of geometry skills through modeling and problem solving in the real world; (f) to develop the use of ICT skills in the context of geometry; (g) to ensure a positive attitude towards mathematics and; (h) to develop an awareness of the historical and cultural heritage of geometry in society and contemporary applications of geometry. However some testimony from the field showed that the results of learning geometry in Indonesia remain low because there are many students who have difficulty in learning geometry, ranging from elementary to university level [4] while Syahputra's [5] statement that students find many difficulties to understans object or image wake geometry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of learning geometry at school as reported by Thomas [3], such (a) to develop spatial awareness, intuition and the ability to visualize geometry; (b) To provide the breadth of experience both in the geometry of two-dimensional space and 3-dimensional; (c) To develop knowledge and understanding and the ability to use the properties and geometry theorem; (d) to encourage the development and use of conjecture, deductive reasoning and evidence; (e) To develop the application of geometry skills through modeling and problem solving in the real world; (f) to develop the use of ICT skills in the context of geometry; (g) to ensure a positive attitude towards mathematics and; (h) to develop an awareness of the historical and cultural heritage of geometry in society and contemporary applications of geometry. However some testimony from the field showed that the results of learning geometry in Indonesia remain low because there are many students who have difficulty in learning geometry, ranging from elementary to university level [4] while Syahputra's [5] statement that students find many difficulties to understans object or image wake geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, according to Budiarto stated that "the purpose of learning geometry is to develop the ability to think logically, develop spatial intuition, imparting knowledge to support other materials, and able to read and interpret mathematical arguments" [4]. Therefore, developing the students' spatial ability is important because it is one of the goals of learning geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Pembelajaran geometri dapat mengembangkan kemampuan pemecahan masalah dan pemecahan masalah merupakan salah satu alasan utama untuk belajar matematika (Walle, 1990). Dengan belajar geometri siswa diharapkan dapat menjadi pemecah masalah yang baik (Abdussakir, 2012). Oleh karena itu, dengan belajar geometri siswa diharapkan dapat menganalisis masalah, memecahkan masalah dan membangun suatu hubungan antara matematika dan kehidupan sehari-hari.…”
Section: Pendahuluanunclassified
“…Sedangkan di perguruan tinggi, berdasarkan pengalaman, pengamatan dan penelitian ditemukan bahwa kemampuan mahasiswa dalam melihat ruang dimensi tiga masih rendah. Bahkan dari berbagai penelitian, masih ditemukan mahasiswa yang menganggap gambar bangun ruang sebagai bangun datar, mahasiswa masih sulit menentukan garis bersilangan dengan berpotongan, dan belum mampu menggunakan perolehan geometri SMU untuk menyelesaikan permasalahan geometri ruang (Abdussakir, 2009). Menurut Abdussakir (2009) bahwa pada dasarnya geometri mempunyai peluang yang lebih besar untuk dipahami siswa dibandingkan dengan cabang matematika lain.…”
Section: Pendahuluanunclassified